The Resilience of Catholic Migrant Workers' Marriages: Socio-Religious Challenges in South Malang, Indonesia - Lamatokan, Yohanes Victor Baro Bitan; Raharso, Alphonsus Tjatur (Potret Pemikiran, 2024)
This study examines the resilience of Catholic migrant workers' marriages in South Malang, Indonesia, within a diverse socio-religious context. The research aims to explore the challenges faced by Catholic couples in maintaining long-distance marriages and to analyze the strategies they employ to preserve marital harmony. Utilizing a qualitative approach with phenomenological methods, this study involves in-depth interviews with two Catholic couples, one of whom works as a migrant worker. The results indicate that couples face dual challenges: economic pressures driving migration and the complexity of maintaining religious identity as a minority. Strategies employed include intensive communication, strengthening faith, and involvement in church communities. Analysis using "superdiversity" and "lived religion" theories reveals how couples negotiate their Catholic identity in a diverse social context. The discussion highlights the importance of contextual pastoral support and interfaith dialogue. In conclusion, the resilience of Catholic marriages in the context of migration and diversity requires complex negotiation between religious teachings, socio-economic realities, and personal interpretations, potentially contributing to broader social harmony.